Comparative Effects of Chloride Channel Inhibitors on LRRC8/VRAC-Mediated Chloride Conductance - Friard, Jonas; Tauc, Michel; Cougnon, Marc; Compan, Vincent; Duranton, Christophe; Rubera, Isabelle (Frontiers in Pharmacology, 2017)
Chloride channels play an essential role in a variety of physiological functions and in human diseases. Historically, the field of chloride channels has long been neglected owing to the lack of powerful selective pharmacological agents that are needed to overcome the technical challenge of characterizing the molecular identities of these channels. Recently, members of the LRRC8 family have been shown to be essential for generating the volume-regulated anion channel (VRAC) current, a chloride conductance that governs the regulatory volume decrease (RVD) process. The inhibitory effects of six commonly used chloride channel inhibitors on VRAC/LRRC8-mediated chloride transport were tested in wild-type HEK-293 cells expressing LRRC8 proteins and devoid of other types of chloride channels (CFTR and ANO1/2). We explored the effectiveness of the inhibitors using the patch-clamp whole-cell approach and fluorescence-based quantification of cellular volume changes during hypotonic challenge. Both DCPIB and NFA inhibited VRAC current in a whole-cell configuration, with IC50 values of 5±1 µM and 55±2 µM, respectively. Surprisingly, GlyH-101 and PPQ-102, two CFTR inhibitors, also inhibited VRAC conductance at concentrations in the range of their current use, with IC50 values of 10±1 µM and 20±1 µM, respectively. T16Ainh-A01, a so-called specific inhibitor of CaCC, blocked the chloride current triggered by hypo-osmotic challenge, with an IC50 of 6±1 µM. Moreover, RVD following hypotonic challenge was dramatically reduced by these inhibitors. CFTRinh-172 was the only inhibitor that had almost no effect on VRAC/LRRC8-mediated chloride conductance. All inhibitors tested except CFTRinh-172 inhibited VRAC/LRRC8-mediated chloride conductance and cellular volume changes during hypotonic challenge. These results shed light on the apparent lack of chloride channel inhibitors specificity and raise the question of how these inhibitors actually block chloride conductances.